El malestar. La narrativa de mujeres en la España contemporánea - Potok, Magda (Wydawnictwo Naukowe UAM, 2010)
The book is devoted to the analysis of the literary prose of contemporary Spanish women writers and presents a collection of themes, motifs, plot schemes, types of characters and the like, which are characteristic of this prose and which have been arranged according to the problems with which they deal. The analysis of the themes is preceded by a survey of theoretical viewpoints developed by the feminist criticism in reference to categories connected with the women's discourse and also an outline history of the Spanish women's literature. The analysis of texts is divided into three parts. The first one (Opresión) presents "common spaces" of women's prose connected with the experience of violence, oppression and discrimination. In the second part (Insatisfacción) the author submits to analysis the traits of crisis occurring in many fields of women's life. In the third part (Transgresión) are recreated the phenomena of subversion - breaking of the existing order and construction of new social and literary models. Works by the most important women writers who have been publishing their books at the turn of the 20th and 21st centuries are studied. These are: Josefina Aldecoa, Lucía Etxebarria, Adelaida García Morales, Laura Freixas, María Laura Espido Freire, Belén Gopegui, Almudena Grandes, Carmen Martín Gaite, Marina Mayoral, Rosa Montero, Carmen Posadas, Soledad Puértolas, Rosa Regás, Ana Rossetti, Fanny Rubio, Clara Sánchez, Maruja Torres, Esther Tusquets and other women writers.

Książka poświęcona jest analizie prozy literackiej współczesnych pisarek hiszpańskich. Autorka przedstawia usystematyzowany zbiór istotnych dla tej prozy tematów, motywów, schematów fabularnych, typów postaci etc. Analizę tematyczną poprzedza wnikliwy przegląd teoretycznych stanowisk wypracowanych przez krytykę feministyczną w odniesieniu do kategorii związanych z dyskursem kobiecym, a także historyczny zarys hiszpańskiej literatury kobiet.